Complementary Role of Thyroid Scintigraphy, Neck Ultrasonography and Biochemical Assay to Delineate Thyroid Disease Pattern in Southern Part of Dhaka (Bangladesh Journal of Nuclear Medicine, 2023)
Thyroid disorders are among the most common endocrinopathies, and a wide array of patients are referred to Nuclear Medicine (NM) institutes for different thyroid-related investigations. In this study, we analyzed the findings of thyroid scintigraphy, high-resolution thyroid gland ultrasound, and thyroid hormone assays of 279 referred patients in the thyroid division of the Institute of Nuclear Medicine and Allied Sciences (INMAS), Mitford. The complementary role of the aforementioned investigations not only helped portray the pattern of thyroid disease in the historic southern part of Dhaka but also once again emphasized the importance of multidisciplinary diagnostic tools in disease management.Bangladesh J. Nuclear Med. 26(1): 31-33, 2023